2006
DOI: 10.1253/circj.70.304
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Second Derivative of the Finger Photoplethysmogram for the Estimation of the Risk of Coronary Heart Disease in the General Population

Abstract: oronary heart disease (CHD) is still one of the major causes of deaths in Japan. 1 Moreover, CHD mortality is expected to increase in the near future because the lifestyles of the Japanese, such as their dietary habits, have become westernized. 2 Indeed, it has been reported that young Japanese patients with CHD who have multiple coronary risk factors, including hypertension, hyperlipidemia, and obesity, all of which might be associated with their lifestyles, have been increasing. 3 Therefore, it is important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 31 publications
4
68
0
Order By: Relevance
“…Among these variables, age is an important factor affecting aortic stiffness; SBP is influenced by the stiffness of large arteries, 27 and SBP continues to rise until the eighth or ninth decade. 28 Our findings suggested that vascular aging-like mechanisms, which include increased arterial stiffness and increased peripheral vascular resistance, 6 occurred during induction of sevoflurane anesthesia. This finding is considered to be mainly due to increased cardiac sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Among these variables, age is an important factor affecting aortic stiffness; SBP is influenced by the stiffness of large arteries, 27 and SBP continues to rise until the eighth or ninth decade. 28 Our findings suggested that vascular aging-like mechanisms, which include increased arterial stiffness and increased peripheral vascular resistance, 6 occurred during induction of sevoflurane anesthesia. This finding is considered to be mainly due to increased cardiac sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 68%
“…The d/a represents a reflection wave from the periphery and is used as an index of peripheral vascular resistance or left ventricular after-load. 6 The AGI, which is defined as the equation of (b-c-d-e)/a, is associated with atherosclerotic alterations, which are based on the history of coronary heart disease, peripheral vascular disease, stroke or abdominal aortic aneurysm, and therefore, it is used as an index of vascular aging. 1 However, the clinical significance of c/a is not well understood.…”
Section: Sdptg and Induction Of Anesthesiamentioning
confidence: 99%
See 2 more Smart Citations
“…The power spectrum of the HRV was divided into very-low-frequency (VLF; 0.003-0.04 Hz), low-frequency (LF; 0.04-0.15 Hz) and high-frequency (HF; 0.15-0.40 Hz) bands. These parameters tional properties of large and peripheral arteries 2) . The a-wave (initial positive wave) and b-wave (initial negative wave) correspond to the early systolic component of the PTG, while the c-wave (re-increasing wave) and d-wave (late re-decreasing wave) correspond to the late systolic component 3) .…”
Section: Methodsmentioning
confidence: 99%